Time-mortality relationships for Cadra (Ephestia) cautella infesting walnut (Juglans regia) using thermal treatments - THAKUR, MANJU; BHALLA, SHASHI; RAWAT, SUDHIR; SINGH, SUBADAS; KHETARPAL, R K (The Indian Journal of Agricultural Sciences, 2011)
Laboratory experiments were conducted at National Bureau of Plant Genetic Resource, New Delhi during 2008â€“09 to determine the time-mortality response relationship of different developmental stages of Cadra (Ephestia) cautella (Wolker), viz egg, early larva, late larvae, pupa and adult infesting kernel and in-shell walnut kernel exposed to thermal treatment at 50Â°C for different durations. Mortality of each stage increased with the increase in exposure time. Egg was found to be the most tolerant stage, followed by late larva, early larva, pupa and adult. The 99% (LT99) mortality of early larva, late larva and pupa in kernel and in-shell walnut kernel was achieved within